Temperature-sensitive mutants of reovirus type 3: evidence for aberrant mu 1 and mu 2 polypeptide species. - Cross, R K (1976)
An analysis of reovirus-specific polypeptides in cells infected with temperature-sensitive mutants under permissive and nonpermissive conditions revealed the presence of (i) all the known viral polypeptides and (ii) aberrant migration of the mu 1 and mu 2 polypeptides in four groups of mutants.